2009
DOI: 10.3892/or_00000389
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of organohalogen compounds and titres of antibodies to Epstein-Barr virus antigens and the risk for non-Hodgkin lymphoma

Abstract: Abstract. Exposure to some pesticides and persistent organic pollutants (POPs) has been indicated to be a risk factor for non-Hodgkin's lymphoma (NHL). Epstein-Barr virus (EBV) has been associated with some subgroups of NHL. In a previous study we found an interaction between high concentrations of some POPs and titres of antibodies to EBV early antigen (EA IgG) in relation to NHL. In the present study we measured lipid adjusted plasma concentrations of 35 congeners of polychlorinated biphenyls (PCB), p,p'-dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 25 publications
3
53
1
Order By: Relevance
“…Of these 11 studies, 7 measured chlordane/heptachlor or their metabolite (eg, oxychlordane, heptachlor epoxide) concentrations. Four studies 55,60,126,127 observed positive associations between chlordanes and NHL, whereas the 3 other studies did not observe an association. 48,54,58 In addition to oxychlordane and related compounds (eg, heptachlor), 10 of these studies examined the association between concentrations of DDT or its metabolite, DDE, and NHL.…”
Section: Prostate Cancermentioning
confidence: 89%
See 3 more Smart Citations
“…Of these 11 studies, 7 measured chlordane/heptachlor or their metabolite (eg, oxychlordane, heptachlor epoxide) concentrations. Four studies 55,60,126,127 observed positive associations between chlordanes and NHL, whereas the 3 other studies did not observe an association. 48,54,58 In addition to oxychlordane and related compounds (eg, heptachlor), 10 of these studies examined the association between concentrations of DDT or its metabolite, DDE, and NHL.…”
Section: Prostate Cancermentioning
confidence: 89%
“…48,54,58 In addition to oxychlordane and related compounds (eg, heptachlor), 10 of these studies examined the association between concentrations of DDT or its metabolite, DDE, and NHL. Five studies 48,55,60,126,127 demonstrated either positive or suggestive associations, whereas the other 5 studies 46,54,56,59,131 did not observe an association between DDT or DDE and NHL.…”
Section: Prostate Cancermentioning
confidence: 98%
See 2 more Smart Citations
“…We found evidence of some confounding by NDL-PCBs, although the risk of NHL associated with TEQ concentrations remained elevated. Epstein-Barr virus (EBV) serology was not performed because an interaction between EBV and organochlorines (Rothman et al, 1997;Hardell et al, 2001;Hardell et al, 2009) would not have been apparent, due to the limited number of participants.…”
Section: Discussionmentioning
confidence: 99%